Mechanical properties of epoxy composites with plasma-modified rice-husk-derived nanosilica. (20th December 2017) - Hubilla, Fatima Athena D.; Panghulan, Glenson R.; Pechardo, Jason; Vasquez, Magdaleno R.
Abstract: In this study, we explored the use of rice-husk-derived nanosilica (nSiO2 ) as fillers in epoxy resins. The nSiO2 was irradiated with a capacitively coupled 13.56 MHz radio frequency (RF) plasma using an admixture of argon (Ar) and hexamethyldisiloxane (HMDSO) or 1, 7-octadiene (OD) monomers. The plasma-polymerized nSiO2 was loaded at various concentrations (1–5%) into the epoxy matrix. Surface hydrophobicity of the plasma-treated nSiO2 -filled composites increased, which is attributed to the attachment of functional groups from the monomer gases on the silica surface. Microhardness increased by at least 10% upon the inclusion of plasma-modified nSiO2 compared with pristine nSiO2 –epoxy composites. Likewise, hardness increased with increasing loading volume, with the HMDSO-treated silica composite recording the highest increase. Elastic moduli of the composites also showed an increase of at least 14% compared with untreated nSiO2 -filled composites. This work demonstrated the use of rice husk, an agricultural waste, as a nSiO2 source for epoxy resin fillers.